Bronchiectasis in PCD looks different to CF on CT scan - Philip Robinson; Lucy Morgan (Multidisciplinary Respiratory Medicine, 2018)
Abstract Background The contemporary diagnosis of bronchiectasis requires CT scanning to describe specific structural lung changes. Scoring systems have been designed and validated in some specific causes of bronchiectasis to allow investigators to correlate CT changes with other indices of disease severity, to describe changes over time, with exacerbation and in response to treatment. Several scoring systems have been developed for CF including the Bhalla Score, Brody score, and the Helbich score. These scoring systems have also been applied to other causes of bronchiectasis including Primary Ciliary Dyskinesia (PCD). This assumes that the nature of structural lung disease in these conditions, as well as the rate and nature of longitudinal changes are identical to, or at least very similar to, those found in CF. This assumption has not been tested. The underlying pathophysiology of PCD is not the same as CF and may cause bronchiectasis that is radiologically similar but not necessarily the same as CF or any other cause of bronchiectasis. The development of a disease specific scoring system for structural change in cases of non-CF bronchiectasis due to any cause, would require consideration of the full range of changes seen in that condition without reference to changes seen in other conditions. We present a summary of structural findings that have been described in PCD and highlight the radiological differences between PCD and other causes of bronchiectasis. We suggest that a PCD specific CT scoring system is required to properly describe changes seen in PCD.